Comparative Study of Silver Nanoparticles Coated and Uncoated NiO–Fe2O3–CaO–SiO2–P2O5 Ferromagnetic Bioactive Ceramics. Issue 11 (8th July 2016) - Anand, Vikas; Singh, Kanwarjit; Kaur, Kulwinder; Kaur, Harpreet; Bhatia, Gaurav; Singh, Sukhdev; Arora, Daljit Singh
Abstract : Bioactive ferromagnetic ceramics of system x NiO–(3− x )Fe2 O3 –52CaO–30SiO2 –15P2 O5, ( x = 0, 3 mol%) have been prepared in the laboratory using sol–gel technique. Silver nanoparticles coating has been undertaken on the surface of synthesized samples. Comparative study of silver nanoparticles coated and uncoated samples has been undertaken with the help of transmission electron microscopy, X‐ray diffraction (XRD), degradation, drug delivery, hemolysis, antimicrobial, and cell culture studies. XRD patterns indicate the growth of hydroxyl apatite layer on the surface of coated as well as uncoated samples. Ferromagnetic properties of samples have been investigated with the help of vibrating sample magnetometer technique. Samples have shown good response as drug carriers under normal conditions as well as under the influence of magnetic field. Drug release mechanism and mesoporus nature of samples have been investigated with the help of Brunauer–Emmett–Teller technique. Nonreactivity of samples (coated and uncoated) with red blood cells and white blood cells show nontoxic nature of the samples. Coated samples have shown better antimicrobial properties against six different microorganisms, including some resistive strain like methicillin‐resistant Staphylococcus aureus with minimum inhibitory concentration of 0.05 mg/ml as compared to uncoated samples. It has been observed that samples also provide a healthy environment for the growth of MG 63 cell lines. It has been noticed that presence of silver nanoparticles on the surface of samples improve degradation and antimicrobial properties.